1994
DOI: 10.1002/art.1790070305
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance characteristics of women with fibromyalgia

Abstract: Objective. The aim of this study was to examine physical performance in women with fibromyalgia (FM) using methods that are easy to use in clinical settings and to compare our findings with published norms or a healthy comparison group. Methods. Measures of shoulder pain and range-ofmotion, isometric shoulder endurance, neck rotation, leg strength, hand grip strength, back flexibility, 6-minute walk distance, and symptom duration were completed on 97 subjects with FM. The comparison group was 30 age-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 21 publications
4
59
1
3
Order By: Relevance
“…In the present study, it was verified that women with FM walked shorter distances than the control group, corroborating the results of previous studies 4,13 . The mean walked distance reported in this study was similar to the mean identified in other investigations of the same patient population 5,9,23 . In relation to the predicted distance, both groups walked significantly less than the expected according to the equation of Enright and Sherrill 7 .…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, it was verified that women with FM walked shorter distances than the control group, corroborating the results of previous studies 4,13 . The mean walked distance reported in this study was similar to the mean identified in other investigations of the same patient population 5,9,23 . In relation to the predicted distance, both groups walked significantly less than the expected according to the equation of Enright and Sherrill 7 .…”
Section: Discussionsupporting
confidence: 90%
“…Measures of workload during maximal cycle tasks have also been reported to be significantly lower in adult FM patients when compared with healthy controls (10). Other measures of fitness such as flexibility scores, strength, and walking distances also appear to be significantly lower in FM patients when compared with historic norms and agesex-matched controls (11). Chronic deconditioning leading to decreased physical activity participation has been suggested to contribute to the severity of symptoms and functional disability commonly reported in FM (2,8,9,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 96%
“…Mannerkorpi et al, had evaluated physical performance in FMS and healthy controls with physical performance tests. As a result, patients with FMS had reduced at physical performance capabilities [17].…”
Section: Citation: Harman H öNeş K Ayna Ab (2015) the Effects Of Hamentioning
confidence: 99%
“…FMS patients have less physical and psychological condition compared with normal population [4]. Decreasing on functional muscle strength and endurance have shown in age-and sex-controlled studies [5,6]. In this study we aimed to investigate the possible relationship between clinical findings, hand grip strength and quality of life in patients with FMS.…”
Section: Introductionmentioning
confidence: 99%